Features of circulation liability of pay check - Кулик, Д. О. (Theory and practice of jurisprudence, 2016)
The analysis of theoretical principles and regulations of features of circulation liability of pay check is made, also it was determined ways of improving them in the context of intensifying the use of cashless payments in civil circulation